SANOGENIC THINKING DEVELOPMENT: PSYCHOLOGICAL, PEDAGOGICAL, AND TECHNOLOGICAL APPROACHES (TAMADDUN NURI JURNALI, 2025)
This study examines the role of sanogenic thinking in enhancing intellectual and emotional well-being. By analyzing various psychological, pedagogical, and technological approaches, the research identifies effective methods for its development. The findings reveal that a combination of psychological training, problem-based learning, reflective thinking techniques, and digital tools significantly contribute to stress resilience, cognitive adaptability, and emotional regulation. The study underscores the necessity of an integrated approach to optimizing sanogenic thinking in educational environments.